2021
DOI: 10.1111/asj.13508
|View full text |Cite
|
Sign up to set email alerts
|

The effect of leucaena hay as a source of effective fibre and nutrients in diets with forage palm for finishing sheep in semi‐arid regions

Abstract: The forage palm (Nopalea cochenillifera 'Miúda') is well adapted to the climate of semi-arid regions and a strategic source of water and energy for ruminant animals (Pinho et al., 2018). It has low levels of dry matter (DM) (142.0 g/kg), crude protein (CP) (33.8 g/kgDM) and neutral detergent fibre (NDF) (267.0 g/kgDM), and a high proportion of non-fibrous carbohydrates (NFC), 567.0 g/kgDM (Cardoso et al., 2019).Supplying forage palm as exclusive feed to ruminants can lead to acidosis, a metabolic disorder whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, despite the lower DMI of animals with 70% hay, the nitrogen accretion in animal's body, which indicates weight gain, it was not altered by treatments. Similarly, Moreira et al (2020), evaluating different proportions of cactus pear and leucaena hay in the diet of rams, did not nd differences in nitrogen retention.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, despite the lower DMI of animals with 70% hay, the nitrogen accretion in animal's body, which indicates weight gain, it was not altered by treatments. Similarly, Moreira et al (2020), evaluating different proportions of cactus pear and leucaena hay in the diet of rams, did not nd differences in nitrogen retention.…”
Section: Discussionmentioning
confidence: 84%
“…The literature (Moreira et al, 2020) showed the potential of this association for sheep. Thus, suppose it would also be applied to cattle.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There has been much recent focus on protein in ruminant feeding because of efforts to reduce costs of ruminant production and concerns arising from climatic aberration. The diversity of the protein source in livestock diets including legumes, grains, food‐industrial by‐products originated from plants is a considerable importance, and those researches must be developed due to the increasing demand for protein rich feedstuff (Chiou et al, 1995; Moreira et al, 2021; Wilkins & Jones, 2000).…”
Section: Introductionmentioning
confidence: 99%